Edukasi Pangan Lokal untuk Pencegahan Anemia pada Remaja di SMAS Adhyaksa 1 - Nurita, Suci Rahmani; Julaecha, Julaecha; Nurfitriani, Nurfitriani; Sari, Mila Triana (Jurnal Abdimas Kesehatan (JAK), 2025)
Anemia in teenagers can cause fatigue quickly, decreased study concentration resulting in low learning achievement and can reduce work productivity. Many factors influence the occurrence of anemia. One of the factors that influences the occurrence of anemia is iron deficiency. Foods that can increase iron absorption, especially nonheme iron, are vitamin C and certain animal protein sources, such as meat and fish. The aim of implementing this educational activity is to increase knowledge. This activity will be carried out from September 2023 to February 2024, starting with identifying partner problems and educational activities for young women. Material is provided through lectures, discussions with participants. Evaluation of young women's knowledge is assessed by conducting a pretest and posttest with the same questions. This activity was attended by 241 students of SMAS Adhyaksa 1 Jambi City. The results of the evaluation during the educational process showed that participants seemed enthusiastic about the counseling material, participants listened to the counseling carefully and participants asked questions regarding material that was unclear. The pre-test and post-test results showed an increase in participants' knowledge from before the activity and after the educational activity by 1-3 points.